ANALISIS PENERAPAN METODE ROLE PLAY TERHADAP KEMAMPUAN BERBICARA SISWA KELAS VI UPT SPF SD NEGERI 101812 NAMO TUALANG - Luvita Para Wansa; Sutikno; Sutarini; Dara Fitrah Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Role Play method in Indonesian language learning and to analyze students' responses and participation in developing the communication skills of sixth-grade students at UPT SPF SD Negeri 101812 Namo Tualang. The study employed a qualitative approach with a descriptive research design. The participants consisted of one sixth-grade teacher and 25 students selected through purposive sampling. Data were collected through observation, interviews, documentation, and field notes. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that the implementation of the Role Play method created an active, interactive, and enjoyable learning atmosphere. Most students demonstrated increased speaking confidence, self-confidence, and the ability to express opinions through role-playing activities. In addition, students became more enthusiastic and actively involved in the learning process. However, several obstacles were still found, such as students who lacked self-confidence, less optimal time management, and differences in participation levels among students. Based on the findings, it can be concluded that the Role Play method contributes positively to the development of sixth-grade students' communication skills, particularly in speaking, interacting, and expressing ideas more confidently.